Expression And Subcellular Localization Of P300 And Its Relation To Proteins Involved In Breast Cancer Progression - Gallardo, Guillermina Ana (2024)
Breast cancer (BC) is a heterogeneous disease that includes dif- ferent molecular and clinical subtypes. Triple negative BC (TNBC) is a molecular subtype of BC that is known for having a poor prognosis and limited therapeutic options. Therefore, it is necessary to investigate potential tumor markers and therapeutic targets for this pathology. Previously, we have demonstrated that inhibition of p300 has an antitumoral effect in BC and TNBC cell lines, and decreases tumor progression in the animal models. In addition, we show that the presence of p300 in the cytoplasm correlates with increased survival of patients suggesting that its nuclear localization is necessary for the pro-tumoral effects. Therefore, we proposed to investigate the expression and localization of p300 and its association with proteins involved in tumor progression of BC and TNBC by immunohistochemistry. In human BC biopsies, we observed a positive association between p300 expression and Elf5, β-catenin, GEF-H1 and HO-1 protein (p<0.05). In human TNBC biopsies, higher p300 levels were associated with decreased nuclear β-catenin and increased membrane β-catenin expression (p<0.05); furthermore, higher cytoplasmic p300 levels correlated with higher E-cadherin expression (p<0.05). In a murine syngeneic model of LM3 cells we detected an increase in E-cadherin and Elf5 expression and a decreased in cytoplasmic β-catenin expression in tumors of animal injected with p300 genetically-silenced cells compared to the control group (p<0.05). In a murine xenograft model of MDA-MB-231 cells, we detected an increase in membrane β-catenin and E-cadherin expression in the tumors of animals injected with VV59 (a specific pharmacological inhibitor of p300) compared to the control group (p<0.05). These results show a positive association between p300 expression and proteins involved in tumor progression in BC. They also demon- strate an antitumor effect for inhibition and cytoplasmic translocation of p300 in TNBC.